Xenomonitoring of Mosquitoes (Diptera: Culicidae) for the Presence of Filarioid Helminths in Eastern Austria - Sarah Susanne Übleis; Claudia Cuk; Michaela Nawratil; Julia Butter; Ellen Schoener; Adelheid G. Obwaller; Thomas Zechmeister; Georg G. Duscher; Franz Rubel; Karin Lebl; Carina Zittra; Hans-Peter Fuehrer (Canadian Journal of Infectious Diseases and Medical Microbiology)
Information on mosquito-borne filarioid helminths in Austria is scarce, but recent discoveries of Dirofilaria repens indicate autochthonous distribution of this parasite in Eastern Austria. In the current xenomonitoring study, more than 48,000 mosquitoes were collected in Eastern Austria between 2013 and 2015, using different sampling techniques and storage conditions, and were analysed in pools with molecular tools for the presence of filarioid helminth DNA. Overall, DNA of D. repens, Setaria tundra, and two unknown filarioid helminths were documented in twenty mosquito pools within the mitochondrial cox1 gene (barcode region). These results indicate that S. tundra, with roe deer as definite hosts, is common in Eastern Austria, with most occurrences in floodplain mosquitoes (e.g., Aedes vexans). Moreover, DNA of D. repens was found in an Anopheles plumbeus mosquito close to the Slovakian border, indicating that D. repens is endemic in low prevalence in Eastern Austria. This study shows that xenomonitoring is an adequate tool to analyse the presence of filarioid helminths, but results are influenced by mosquito sampling techniques, storage conditions, and molecular protocols.